Peran Komunikasi Organisasi dalam Meningkatkan Efektivitas Pengawasan Internal di Inspektorat Kabupaten Jember - Hersa Farida Qoriani; Tira Anggraini; Novita Ayu Safitri; Nila Varadisa (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This research aims to comprehensively analyze the role of organizational communication in improving the effectiveness of internal supervision at the Jember Regency Inspectorate. The study also emphasizes how communication patterns contribute to strengthening coordination between structural units in supervisory practices. Utilizing a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation involving leadership and auditors, allowing for a rich and contextual understanding of supervisory processes. The results indicate that organizational communication serves as a significant booster factor for supervisory effectiveness. Transparent information flow enhances auditor comprehension, while the regulative function ensures compliance with Standard Operating Procedures (SOP). These communication mechanisms also support consistency in implementing supervisory tasks across different units. Furthermore, persuasive and integrative communication proved effective in reducing resistance from supervision objects, thereby fostering a dialogic and conducive working environment and improving mutual understanding between stakeholders. The study concludes that the integration of sound communication management is an absolute prerequisite for establishing clean and transparent government governance, particularly in strengthening accountability and public sector performance within local government institutions.